When a Canadian is not a Canadian: marginalization of IMGs in the CaRMS match - MacFarlane, Malcolm M (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
This paper explores the marginalization experienced by International Medical Graduates (IMGs) in the Canadian Residency Matching Service (CaRMS) Match. This marginalization occurs despite all IMGs being Canadian citizens or permanent residents, and having objectively demonstrated competence equivalent to that expected of a graduate of a Canadian medical School through examinations such as the MCCQE1 and the National Assessment Collaboration OSCE. This paper explores how the current CaRMS Match works, evidence of marginalization, and ethnicity and human rights implications of the current CaRMS system. A brief history of post graduate medical education and the residency selection process is provided along with a brief legal analysis of authority for making CaRMS eligibility decisions. Current CaRMS practices are situated in the context of Provincial fairness legislation, and rationalizations and rationales for the current CaRMS system are explored. The paper examines objective indicators of IMG competence, as well as relevant legislation regarding international credential recognition and labour mobility. The issues are placed in the context of current immigration and education policies and best practices. An international perspective is provided through comparison with the United States National Residency Matching Program. Suggestions are offered for changes to the current CaRMS system to bring the process more in line with legislation and current Canadian value systems, such that “A Canadian is a Canadian.”